The Influence of Amicus Curiae Briefs on U.S. Supreme Court Opinion Content. Issue 4 (28th October 2015) - Collins, Paul M.; Corley, Pamela C.; Hamner, Jesse
Abstract : We address fundamental questions about the ability of interest groups to shape public policy by examining the influence of amicus curiae briefs on U.S. Supreme Court majority opinion content. We argue that the justices will incorporate language from amicus briefs into their opinions based on the extent to which the amicus briefs contribute to their ability to make effective law and policy. Using plagiarism detection software and other forms of computer assisted content analysis, we find that the justices adopt language from amicus briefs based primarily on the quality of the brief's argument, the level of repetition in the brief, the ideological position advocated in the brief, and the identity of the amicus. These results add fresh insight into how interest groups influence the development of federal law by the Supreme Court.